2013
DOI: 10.1089/thy.2013.0194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Prostaglandin Fon Adipocyte Biology Relevant to Graves' Orbitopathy

Abstract: Background: In Graves' orbitopathy (GO), increased proliferation, excess adipogenesis, and hyaluronan overproduction produce GO exophthalmos. Enophthalmos occurs in some glaucoma patients treated with Bimatoprost (prostaglandin F 2a , PGF 2a ) eye drops. We hypothesized that enophthalmos is secondary to reductions in orbital tissue proliferation, adipogenesis, and/or increased lipolysis. We aimed to determine which of these is affected by PGF 2a by using the 3T3-L1 murine preadipocyte cell line and primary hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 33 publications
(33 reference statements)
2
13
1
Order By: Relevance
“…The standard deviation was consistent with power calculations suggesting that we were not underpowered and unlikely that the effect was missed. This is in contrast with the in vitro findings (20,21), anecdotal case reports in people without GO (6)(7)(8) suggesting adipocyte differentiation inhibition with…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…The standard deviation was consistent with power calculations suggesting that we were not underpowered and unlikely that the effect was missed. This is in contrast with the in vitro findings (20,21), anecdotal case reports in people without GO (6)(7)(8) suggesting adipocyte differentiation inhibition with…”
Section: Discussioncontrasting
confidence: 96%
“…Adipogenesis starts early in the disease and it has been shown that it may continue even in the inactive disease stage (23). PGF2α inhibits adipogenesis per se but does not affect lipolysis and hence has no impact on an already fully mature adipocyte (20). Not all glaucoma patients treated with PGF2α develop periorbital fat atrophy with an estimated incidence of 24.1% (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In addition, 1 group of investigators has shown that in a mouse model of thyroid eye disease (TED), the doubling time of orbital fibroblasts was increased when the cells were exposed in vitro to PGF2α analogues. 4 This suggests that the PGF 2α analogues may decrease adipogenesis and thus induce fat atrophy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…3 Other reports have shown that exposing orbital fibroblasts to prostaglandin F2α—the common base structure of the 3 major PGA bimatoprost, travoprost, and latanoprost—slowed adipocyte population growth in cell culture by decreasing adipogenesis when compared with cells not exposed to PGA. 4 …”
Section: Introductionmentioning
confidence: 99%